Evaluation of feed budgeting, complete diet blending, and corn-supplement blending on finishing-pig performance - R C Sulabo; G A Papadopoulos; J R Bergstrom; D Ryder; Joel M DeRouchey; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2010)
A total of 283 pigs (PIC TR4 x 1050, initially 77.2 ± 1.4 lb BW) were used to compare phase feeding with blending finishing diets by using the FeedPro system (Feedlogic Corporation, Willmar, MN). There were 3 experimental treatments: (1) a standard 4-phase complete feed program, (2) blending high- and low-lysine complete diets over the entire experiment, and (3) blending ground corn and a separate complete supplement within each phase. FeedPro is an integrated feed dispensing system that can deliver and blend 2 separate diets while dispensing. The 4 phases were 77 to 120, 120 to 175, 175 to 221, and 221 to 278 lb. Each treatment had 12 replicate pens and 8 pigs per pen. Overall (77 to 278 lb), ADG and ADFI were similar (P>0.24) across treatments. However, pigs fed the ground corn-supplement blend had poorer (P<0.01) F/G than pigs fed diets blended in multiple phases and tended to have poorer (P<0.09) F/G than pigs fed the standard phase diets. There were no differences (P>0.70) in HCW, percentage yield, and loin depth across treatments. Pigs fed using phase feeding of the ground corn-supplement blend had greater (P<0.02) percentage lean and lower (P<0.04) fat depth than pigs fed using phase feeding of complete diets or diet blending. There were no (P>0.28) statistical differences in total revenue and income over feed costs (IOFC) across treatments. However, the highest IOFC was obtained from diet blending, which had a numeric advantage of 1.44 to 2.32/pig over other treatments. In conclusion, the FeedPro system blended separate complete diets and a ground corn-supplement combination without adversely affecting growth performance and carcass characteristics.; Swine Day, Manhattan, KS, November 18, 2010
Keywords: Swine Day; 2010; Kansas Agricultural Experiment Station contribution; no. 11-016-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1038; Swine; Carcass characteristics; Feed blending; Growth